Combustion characteristics and quantitative determination of energy release of Epoxy-Al active materials projectile hypervelocity impact steel targets in vacuum environment. (December 2022) - He, Zhenhui; Tang, Enling; Yao, Wenjin; Chen, Chuang; Han, Yafei
Abstract: Epoxy resin is often used to intermediate of structural materials or adhesives as an important raw material and product of modern industry by low density, high strength and easy molding, which plays an important role in the field of composite materials. However, the current research mainly focuses on the mechanical properties of epoxy matrix composites under quasi-static and low strain rate loading, and there is little research on the properties of Epoxy-metal composites under high-speed loading. In this paper, Epoxy-Al5μm (70 wt%/wt30%) samples were prepared by adding active metal aluminum powder to epoxy resin and vacuum curing. The reaction-release energy and combustion characteristics of Epoxy- Al active materials projectile hypervelocity (2.85–3.46 km/s) impact steel targets in vacuum environment were studied by two-stage light gas gun loaded combined with a high-speed camera, an infrared thermal imager, a transient overpressure testing system and a transient optical fiber pyrometer. The results show that the Epoxy- Al material exhibits strong chemical energy release and combustion characteristics under hypervelocity impact load. The energy release can reach 21.36 kJ/g, which is much higher than the existing PTFE/ Al active materials (8.23 kJ/g). The whole reaction process can be divided into three stages: accelerated reaction stage, decelerated reaction stage and after effect stage, a stable combustion phenomenon exists in the deceleration reaction period. In the accelerated reaction stage, the average reaction speed of the Epoxy- Al projectile is 1.4 km/s and the maximum temperature is 1650 K.